Problems of Horizontal and Vertical Political Accountability of Elected Officials in Indonesia - Said, Muhtar; Minan, Ahasanul; Huda, Muhammad Nurul (JILS (Journal of Indonesian Legal Studies), 2021)
The accountability system for elected officials in Indonesia is inherently linked with the electoral system that is applied to unravel the problem in the context of a symmetrical system of people's sovereignty. This article analyzes the dynamics of the current regulations on the accountability system of elected officials. However, this article would only focus on the accountability system for regional leaders (governor, mayor and regent), regional legislators (DPRD) and the senatorial regional delegates (DPD) in Indonesia and the participation of constituencies in proposing a recall system. The purpose of this research is to construct an accountability mechanism for regional heads, DPRD and DPD to their constituents that are appropriate and in line with the electoral system applied in Indonesia. This research is expected to be a material for consideration for policy makers and the Indonesian people in general in designing an accountability system for elected officials that is appropriate and in line with the applied electoral system. To do such, this article is based on a descriptive study. Keywords: accountability, horizontal and vertical politics, direct democracy, elected officials, recall, Indonesian election